The Implementation of the AHE Method to Improve Elementary Students’ Learning Outcomes at AHE Tutoring Center - Sabila, Rahma Riska; Baihaqi, Mohammad (Journal of Educational Research and Practice, 2024)
Many parents do not pay enough attention to their children's growth and development. It is not uncommon for many children to experience difficulties in reading and writing. Not a few children who occupy elementary school feel difficult and lag behind lessons because they are less able to read and write properly and correctly. Therefore, parents choose to enroll their children in tutoring as a solution to the problem. Tutoring is a non-formal education platform that helps children in the development of education outside of school hours. One of them is Anak Hebat (AHE) Tutoring. This tutoring offers an interesting and fun way to learn. The existence of learning accompanied by games makes children not easily bored in learning which is only done for 30 minutes per day. This research uses a qualitative approach through data collection techniques in the form of observation, interviews, and documentation. Researchers want to study more deeply related to improving learning outcomes in the Anak Hebat (AHE) tutoring.